2014
DOI: 10.1093/nar/gku657
|View full text |Cite
|
Sign up to set email alerts
|

Induction and suppression of tick cell antiviral RNAi responses by tick-borne flaviviruses

Abstract: Arboviruses are transmitted by distantly related arthropod vectors such as mosquitoes (class Insecta) and ticks (class Arachnida). RNA interference (RNAi) is the major antiviral mechanism in arthropods against arboviruses. Unlike in mosquitoes, tick antiviral RNAi is not understood, although this information is important to compare arbovirus/host interactions in different classes of arbovirus vectos. Using an Ixodes scapularis-derived cell line, key Argonaute proteins involved in RNAi and the response against … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

16
173
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 129 publications
(189 citation statements)
references
References 65 publications
16
173
0
Order By: Relevance
“…Needless to say that antiviral RNAi was reported also from other hexapods, such as silk moth Zografidis et al, 2015). Antiviral RNAi was also reported for Chelicerata (ticks and mites (Schnettler et al, 2014;Hoy et al, 2016)) or Crustacea (shrimps (Huang and Zhang, 2013;Sabin and Cherry, 2013;Yang et al, 2014b;Jariyapong et al, 2015;Maralit et al, 2015;Hoy et al, 2016).…”
Section: Antiviral Rnaimentioning
confidence: 88%
See 1 more Smart Citation
“…Needless to say that antiviral RNAi was reported also from other hexapods, such as silk moth Zografidis et al, 2015). Antiviral RNAi was also reported for Chelicerata (ticks and mites (Schnettler et al, 2014;Hoy et al, 2016)) or Crustacea (shrimps (Huang and Zhang, 2013;Sabin and Cherry, 2013;Yang et al, 2014b;Jariyapong et al, 2015;Maralit et al, 2015;Hoy et al, 2016).…”
Section: Antiviral Rnaimentioning
confidence: 88%
“…RNAi is functional across other arthropods subphyla, including Chelicerata (ticks and mites (Kurscheid et al, 2009;Schnettler et al, 2014;Hoy et al, 2016)) and Crustacea (shrimps Huang and Zhang, 2013;Sabin and Cherry, 2013;Yang et al, 2014b;Jariyapong et al, 2015;Maralit et al, 2015;Hoy et al, 2016). We did not find published functional RNAi data for Myriapoda but genomic analyses show that they have the necessary machinery (Palmer and Jiggins, 2015).…”
Section: Rnai Pathway In Arthropodsmentioning
confidence: 99%
“…In Culex mosquitoes-the predominant group of WNV vectors-virus-specific siRNAs are highly abundant, whereas viral piRNAs (vpiRNAs) appear to be absent (14,21). For flaviviruses, three putative viral suppressors of RNAi (VSRs) have been identified in vitro: the NS4B and NS3 proteins of DENV type 2 (DENV-2) and the noncoding subgenomic flavivirus RNA (sfRNA) for WNV (22)(23)(24).…”
mentioning
confidence: 99%
“…The conservation of sfRNA production by MBFs, TBFs, and ISFs emphasizes the putative importance of sfRNA production in arthropods (35). So far, it has been demonstrated that sfRNA acts as a suppressor of miRNA-and siRNA-mediated RNAi in vitro in both mammalian and arthropod cells (23,37). The highly abundant sfRNA most likely acts as a decoy substrate for Dicer to prevent it from cleaving other double-stranded RNA (dsRNA) molecules.…”
mentioning
confidence: 99%
“…Although specific Ixodes spp. transcripts have been implicated in TBFV infection in tick cell cultures (46)(47)(48), ex vivo organ cultures can provide a means to more precisely probe tissue-specific vector interactions.…”
mentioning
confidence: 99%